2016
DOI: 10.1038/srep34366
|View full text |Cite
|
Sign up to set email alerts
|

Mapping light-driven conformational changes within the photosensory module of plant phytochrome B

Abstract: Organisms developed different photoreceptors to be able to adapt to changing environmental light conditions. Phytochromes are red/far-red (r/fr) photochromic photoreceptors that belong to the classical photoreceptors along with cryptochromes and phototropins. They convert absorbed light into a biological signal by switching between two states in a light-dependent manner therefore enabling the light control downstream signalling. Their Pfr conformation is the biological active form in plants, but until now only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 51 publications
0
41
0
Order By: Relevance
“…Here, we provide photobiological and physiological evidence that NTE deletion severely enhances thermal reversion of phyB in planta, leading to very low Pfr concentrations even in high light, thus strongly reducing phyB activity (Fig. Deletion of the NTE affected the chromophore and its surrounding hydrogen bonding network, particularly in the Pfr state, which could potentially affect the thermal reversion kinetics, and it was also revealed that the NTE undergoes light-dependent structural changes particularly in the S84-K88 region (Horsten et al, 2016). Until recently there was no structural information about phyB NTE available, as the published crystal structure of Arabidopsis phyB PSM lacks the NTE (Burgie et al, 2014).…”
Section: Researchmentioning
confidence: 79%
“…Here, we provide photobiological and physiological evidence that NTE deletion severely enhances thermal reversion of phyB in planta, leading to very low Pfr concentrations even in high light, thus strongly reducing phyB activity (Fig. Deletion of the NTE affected the chromophore and its surrounding hydrogen bonding network, particularly in the Pfr state, which could potentially affect the thermal reversion kinetics, and it was also revealed that the NTE undergoes light-dependent structural changes particularly in the S84-K88 region (Horsten et al, 2016). Until recently there was no structural information about phyB NTE available, as the published crystal structure of Arabidopsis phyB PSM lacks the NTE (Burgie et al, 2014).…”
Section: Researchmentioning
confidence: 79%
“…This interaction is similar for phyB from A. thaliana and S. bicolor, suggesting that it represents a general characteristic of phyB. All other regions in the NTE with HDX rates altered by photoconversion probably lack direct contact with the chromophore itself [8]. It comprises a perturbation of the hydrogen bonding network and the CD portion of the chromophore, reflected by a shift in the conformational Pfr-I/Pfr-II equilibrium.…”
Section: Discussionmentioning
confidence: 79%
“…The impact of these interactions on the chromophore-binding pocket is small and only observed in the Pfr state. Our packing model for the NTE/PSM interactions suggested that in the Pfr state a stretch with comparably slow intrinsic HDX rates (P28-Q36) may interact with the b1 strand of the GAF domain and its adjacent loop [8] (Fig. Both effects, which most likely constitute the molecular basis for the hypsochromic shift of the electronic absorption in NTE deletion variants (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations